A self-powered and cost-effective rGO/n-Si photodetector with broad spectral response including visible, UV, and near-IR regions - Yilmaz, Mehmet; Yaman, Mehmet; Yildirim, Fatma; Nuhzat, Samsoor; Aydogan, Sakir (Elsevier, 2025)
Schottky-type photodetectors are considered an attractive research focus by researchers due to their simple fabrication process and fast response time. However, optimization of the Schottky barrier height is still considered a major challenge, which is being investigated to improve device performance for visible light sensing applications. The study aims to fabricate a reduced graphene oxide/silicon (rGO/n-Si) Schottky photodetector optimized for high-performance visible light sensing and characterize the diode parameters. The fabricated device exhibited a high ON/OFF ratio of 103, a detection of 5.21 x 1011 Jones (D*) and a responsivity of 700 mA/W (R) under 590 nm illumination. The instrument also demonstrated excellent spectral sensitivity in the UV range with high external quantum efficiency (EQE) exceeding 200 % at 365 nm. The obtained results have demonstrated the potential of rGO as a tunable interfacial material to obtain optimized Schottky junctions in optoelectronic applications and are thought to be instructive for other researchers.
Keywords: rGO; Photodiode; Visible light detection